Pacto nacional pela alfabetização na idade certa: repercussão de uma política de formação docente - Pereira, Jair Joaquim (2018)
This thesis, is based on theoretical and analytical devices from French guidelines Discourse Analysis (DA), analyses the “Pacto Nacional pela Alfabetização na Idade Certa (PNAIC)” proposal, its repercussion and results as a continuing in-school-training for literacy teachers-specifically in Santa Catarina State, focused in the county of Palhoça. This thesis has the PNAIC training books – literacy and language – as analysis sources as well their related training units, the portfolio produced by the literacy teachers, and the reports produced by the study mentors. According to DA perspective, on this thesis the form such materials were produced is not privileged, but how the texts work, producing meaning effects. The analysis of the materials, performed to meet the proposed objectives, suggests that PNAIC adopts the same production conditions, which generated previous policies that cooperates to playback and maintenance of political-ideological speech towards the literacy teacher training. Analyzing, as a political educational document, the units that compound the literacy and language books, this thesis indicates that PNAIC is a public training teachers policy, like so many others implemented by the federal government. In relation to the teacher‟s discursive demonstrations, suggests the underlying discourses to PNAIC moving towards those ones from Pró-letramento, although separated in time and space: both are determined for quite similar production conditions, as the objects (the selected themes, the approached concepts, the subjects), in such a way the PNAIC discourse refers to Pró-letramento discourse. PNAIC has always worked by default from Education Secretary departments, that would have the task to guide in a pedagogic way the literacy practice in schools- that is what this thesis shows after the discursive demonstrations analysis made by the studies mentor. The discursive analysis of relations established by Universidade Federal de Santa Catarina (UFSC) to PNAIC implementation, another goal of the thesis, shows that UFSC is the institution that legitimates the in-school training model to PNAIC standards, constituting as a reference, specially to more fragile municipalities in terms of training, as is the case with Palhoça (SC). Regarding the effects of In-School Training implementation Department Setor de Formação Continuada (SFC), this thesis suggests that, counteracting the working modes of pedagogics, the Setor de Formação Continuada (SFC) practices of training were produced through permanent dialogue between teachers and the trainers, what has transformed schools into singulars training teachers spaces. In particular, the meaning effects that were produced in analyzed materialities, suggests that even with all the investment - only in the case of PNAIC it were R$ 3 billion – broad training policies as PNAIC, do not respond to specific teachers demands in schools, that is why this thesis advocates training policies less ambitious, which cover the municipal area, where the bigger chances such policies respond to local fragilities are. Certainly with such amount of available resources to counties, well succeed experiences like SFC could be enlarged and, thus, change reality education in many other Brazilian municipalities that still depend on federal government when the topic is in-school teachers training.